Práticas de contabilidade gerencial adotadas por empresas participantes do projeto extensão produtiva e inovação na região do Vale do Rio dos Sinos - Mariussi, Eduardo Ezidio (Universidade do Vale do Rio dos Sinos, 2015)
The aim of this study was to evaluate how the companies participating in PEPI – Vale do Rio dos Sinos perform the managerial control. Management accounting has been recognized as a leading feeder of information used by enterprise managers; consists in the process of identification, measurement, analysis and reporting of information on economic events. The study was based on data collection from 198 companies respondents of the initial diagnosis. After the analysis result, it was possible to detect that most companies surveyed conduct the managerial control in a superficial way, being influenced by billing (the higher, the greater the control). On the analysis carried out, both by the comparison of the results and the bibliographical study, it can be concluded that the managerial control must be a practice to be disseminated among small enterprises in order to assist them in expanding their business and profitability.
Keywords: Contabilidade gerencial; Análise; Ferramentas; Management accounting; Analysis; Tools